Five-year Antibody Persistence and Safety After a Single Dose of Combined Haemophilus influenzae Type B Neisseria meningitidis Serogroup C–Tetanus Toxoid Conjugate Vaccine in Haemophilus influenzae Type B-primed Toddlers. Issue 12 (December 2015) - Booy, Robert; Nolan, Terry; Reynolds, Graham; Richmond, Peter; Nissen, Michael; Marshall, Helen; Stoney, Tanya; Van Der Wielen, Marie; Kolhe, Devayani; Miller, Jacqueline M.
Abstract : Background: Antibody persistence is evaluated in healthy Australian children 4 and 5 years postvaccination with a single dose of combined Haemophilus influenzae type b– Neisseria meningitidis serogroup C tetanus toxoid conjugate vaccine (Hib–MenC–TT) compared with separately administered Hib–TT and MenC–CRM197 vaccines (Hib + MCC). Methods: This is another follow-up of a phase III, open, randomized, controlled study (NCT00326118), in which 433 Hib-primed but MenC naïve toddlers aged 12–18 months were randomized 3:1 to receive Hib–MenC–TT or Hib + MCC vaccines. Protection against (1) MenC was measured by serum bactericidal antibody assay using rabbit complement (rSBA) and (2) Hib was measured by enzyme-linked immunosorbent assay of antibodies to polyribosylribitol phosphate (anti-PRP). Study children were assessed for any potentially vaccine-related serious adverse events at each persistence study visit. Results: The according-to-protocol cohorts for persistence at years 4 and 5 included 282 and 263 children, respectively. The percentages of children with rSBA-MenC titers ≥1:8 at years 4 and 5 were 12.5% and 19.0%, respectively, in the Hib–MenC group; and 12.3% and 25.0% in the Hib + MCC group. All children in each group had anti-PRP concentrations ≥0.15 μg/mL at year 5. Exploratory analyses suggested no potential differences between groups in rSBA-MenC or anti-PRP antibody persistence. No vaccine-related serious adverse events were reported. Conclusions: Antibody persistence was similar for years 4 and 5 after Hib–MenC–TT or Hib + MCC vaccination, with the majority of children retaining anti-PRP antibody concentrations ≥0.15 μg/mL at both timepoints. The percentage of children retaining rSBA-MenC titers ≥1:8 was low (⩽25%), suggesting that a MenC booster dose may be warranted before adolescence. Abstract : Supplemental Digital Content is available in the text.